2017
DOI: 10.1155/2017/8682010
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Halitosis in relation to Oral Hygiene Practices, Oral Health Status, General Health Problems, and Multifactorial Characteristics among Workers in Ilala and Temeke Municipals, Tanzania

Abstract: Aim. To assess self-reported halitosis, oral hygiene practices, oral health conditions, general health problems, sociodemographic factors, and behavioural and psychological characteristics among workers in Ilala and Temeke municipals. Materials and Methods. This was a cross-sectional descriptive study. Four hundred workers were recruited using a self-administered structured questionnaire. Results. Self-reported tooth brushing practice was 100%, tongue cleaning 58.5%, dental flossing 4.3%, gum bleeding on tooth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
14
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 36 publications
(51 reference statements)
8
14
1
Order By: Relevance
“…it is safe to assume self-perception as a true patientcentered outcome, which is highly recommended in present research in the health field 6 . In the present study the overall prevalence of halitosis according to the questionnaire (depending on the answer of question one which inquired the students if they have had bad breath to assess the awareness of the students about halitosis), the result was approaching fifty percent, this was almost similar to the results reported in Qassim, Saudi Arabia (19) , which is also lower in comparison to a study done in Kinondoni ( 2013), but at the same time is higher than the findings reported in other populations especially Brazil (8) , USA (1996) (20) . In these studies, the gender had no statistically significant association to the outcome with similar methodology (8) , so the result of the current study could be compared with these studies.…”
Section: Discussionsupporting
confidence: 80%
“…it is safe to assume self-perception as a true patientcentered outcome, which is highly recommended in present research in the health field 6 . In the present study the overall prevalence of halitosis according to the questionnaire (depending on the answer of question one which inquired the students if they have had bad breath to assess the awareness of the students about halitosis), the result was approaching fifty percent, this was almost similar to the results reported in Qassim, Saudi Arabia (19) , which is also lower in comparison to a study done in Kinondoni ( 2013), but at the same time is higher than the findings reported in other populations especially Brazil (8) , USA (1996) (20) . In these studies, the gender had no statistically significant association to the outcome with similar methodology (8) , so the result of the current study could be compared with these studies.…”
Section: Discussionsupporting
confidence: 80%
“…The study showed that most adults brush their teeth for less than 2 minutes; a finding close to that of Miura [16]. However, we should mention that such a time duration is insufficient because dental plaque responsible for dental caries builds up very slowly, and therefore brushing should be two or 3 minutes [17]. The fact that the majority of the adult population uses toothbrush is encouraging from a dental health promotion perspective.…”
Section: Discussionsupporting
confidence: 59%
“…These findings are in line with previous studies from Gilbert and Nutttall (Gilbert & Nuttall, 1999) and Dietrich (Dietrich et al., 2005). Even though halitosis has been shown to be associated with bleeding gums (Kayombo & Mumghamba, 2017), it is possible that the indirect nature of the questions or their potential negative connotation is unhelpful.…”
Section: Discussionmentioning
confidence: 99%